Causal relationship between thyroid dysfunction and hallux valgus: A two-sample Mendelian randomization study - Xiong, Binglang; Bai, Zixing; Cao, Xuhan; Nie, Duorui; Zhang, Cheng; Sun, Xudong; Guo, Ziyan; Wen, Jianmin; Sun, Weidong (Frontiers in Endocrinology, 2023)
Introduction：Previous observational studies have reported that thyroid dysfunction is associated with hallux valgus (HV). However, the causal effect of thyroid dysfunction on hallux valgus is still unknow. To assess whether there is a causal relationship between thyroid dysfunction and hallux valgus, we performed a two-sample Mendelian randomization（MR） study. Methods：The data of two-sample Mendelian randomization study were obtained from public databases. In this study, hypothyroidism, hyperthyroidism, free thyroxine (FT4) and thyrotropin (TSH) were chosen as exposures. The single nucleotide polymorphisms (SNP) of hypothyroidism and hyperthyroidism were from the genome-wide association studies (GWAS) of IEU database, including 337,159 subjects. Data for FT4 and TSH (72,167 subjects) were extracted from the ThyroidOmics Consortium. HV was used as outcome. The SNPs associated with HV were selected from a GWAS of 202,617 individuals of fignngen database. The inverse variance weighted (IVW) method was used as the primary analysis. Four complementary methods were applied, including MR-presso, MR-Egger, Weighted median. In addition, Cochran's Q test, MR-presso, MR-Egger regression and the leave-one-out test were used as sensitivity analysis, and MR-pleiotropy test was performed to examine pleiotropy. Results: According to the results of IVW, we found that there was a causal relationship between hypothyroidism and HV, and hypothyroidism increased the incidence of HV (OR=2.838, 95%CI: 1.116-7.213, p = 0.028). There were no significant causal effects of hyperthyroidism, FT4 and TSH on HV (P>0.05). Sensitivity analyses showed that the results were robust and reliable, and no horizontal pleiotropy was detected. Conclusions：Our findings provided genetic support that hypothyroidism might increase the risk of HV. It will predict the occurrence of HV in patients with hypothyroidism and provide suggestions for early prevention and intervention.